Benefits of using the shaft condylar angle as a guide for close reduction in pediatric supracondylar humeral fractures - Pawaris Sukvanich; Chanavee Jirapornkul; Ronnachit Boonprasert; Pinkawas Kongmalai (Journal of Orthopaedic Reports)
Purpose: The surgical treatment of Gartland types two and three supracondylar humeral fractures is currently recommended. However, post-operative decreases in the range of motion of the elbow are commonly observed. The purpose of this study was to investigate the relationship between shaft condylar angle angle (SCA) and lateral capitellohumeral angle (LCHA) with post-operative range of motion in surgically treated supracondylar humeral fractures. Methods: Patients under the age of 11 with a Gartland type two or three supracondylar humeral fracture who underwent surgery between March 2020 and March 2023 at a tertiary care institution were eligible for this study. Six weeks after surgery, the pediatric orthopedist assessed the range of motion in both the operated and uninjured elbows in terms of flexion and extension. The SCA and LCHA were then measured by the pediatric orthopedist and an orthopedic resident. The measurements were repeated four weeks later. Results: A significant correlation was observed between SCA and elbow flexion in 36 individuals. Subgroup analysis revealed that a difference in SCA of 7.65° from the normal value was associated with a significant difference in the angle of elbow flexion at 6 weeks after surgery. The measurement's reliability was determined to be good for both intra- and inter-observer reliability. Conclusions: The results of this study indicate that SCA is correlated with post-operative loss of elbow flexion and can be used as a tool for post-reduction evaluation. To minimize the loss of elbow flexion after surgery, the SCA should be within 7.65 degrees of the normal value.TCTR20220430007 (Registered 30 April 2022) “retrospectively registered”